Efficient interface prediction-correction method for the solution of multi dimensional parabolic problem over non overlapping subdomains - Daoud, S. Daoud; Gurbuz, Nil (Int Assoc Engineers-Iaeng, 2007)
In this article we present an efficient time lagging interface prediction method with implicit correction (TLIC) for the solution of multi dimensional parabolic problem defined over non overlapping sub-domains. The time lagging method have been implemented with different integral multiples spatial spacing displacements from the interface line(s). We considered the additive splitting up,method with respect to the spatial variables to solve the multi dimensional parabolic problem over each subdomains. The proposed method have been implemented to solve two dimensional model problem over multi non overlapping subdomains with respected to each spatial variable. http://www.iaeng.org/publication/WCE2007/WCE2007_pp772-776.pdf
World Congress on Engineering 2007 -- JUL 02-04, 2007 -- London, ENGLAND
Keywords: non overlapping domain decomposition; time lagging; multi dimensional parabolic equation; parallel splitting